Зависимость содержания витаминов А и Е в печени обыкновенной полевки от возраста и пола животного - Золотухина, С.И. (Вестник зоологии, 1969)
The article deals with the investigation of age changes of A and E vitamin content in the liver of Microtus arvalis Pall, and dependence of its content on the sex of the animal. An increase of the vitamin A concentration with the age was observed. It is established, that the liver of females contains greater amount of A and E vitamins than that of males in all seasons.